A note on Raghavan-Reilly's pairwise paracompactness. (15th July 2000) - Kovár, Martin M.
Abstract : The bitopological unstability ofR R -pairwise paracompactness in presence of pairwise Hausdorff separation axiom is caused by a bitopological property which is much weaker and more local thanR R -pairwise paracompactness. We slightly generalize some Michael's constructions and characterizeR R -pairwise paracompactness in terms of bitopologicalθ -regularity, and some other weaker modifications of pairwise paracompactness.